2018
DOI: 10.1161/strokeaha.118.022057
|View full text |Cite
|
Sign up to set email alerts
|

Validation of the Intracerebral Hemorrhage Score in Uganda

Abstract: Background and purpose: Rates of intracerebral hemorrhage (ICH) are estimated to be highest globally in sub-Saharan Africa (SSA). However, outcomes of ICH are poorly described and standard prognostic markers for ICH have not been validated in the region. Methods: We enrolled consecutive patients with computed tomography (CT)-confirmed ICH at a referral hospital in southwestern Uganda. We recorded demographic, clinical and radiographic features of ICH, and calculated ICH scores. We fit Poisson regression mode… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2

Citation Types

1
4
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(6 citation statements)
references
References 14 publications
1
4
1
Order By: Relevance
“…Initial CT scan of brain has an important role in predicting outcome of patients with ICH. Volume of hematoma was unequivocally seen to be associated with mortality 9,14,17,18,21 ; which is also true for our study. (CAVA) 22 , it is still useful as an rapid and reliable method 23 .…”
Section: Discussionsupporting
confidence: 86%
“…Initial CT scan of brain has an important role in predicting outcome of patients with ICH. Volume of hematoma was unequivocally seen to be associated with mortality 9,14,17,18,21 ; which is also true for our study. (CAVA) 22 , it is still useful as an rapid and reliable method 23 .…”
Section: Discussionsupporting
confidence: 86%
“…So, external validation to determine whether the ICH score could accurately risk-stratify patients in a cohort independent of that from which it was developed was done in different population. Till date several studies in abroad have shown the external validity of ICH score but the study population and the hospital settings were completely different from ours 6,[9][10][11][12][13][14] . Published study on ICH score in Bangladesh is very limited and the external validity of ICH score is not aimed in any study yet.…”
contrasting
confidence: 58%
“…We realized 05 publications from the MURTI trainees in this area: (i) PMC5659749; 34 (ii) PMC7341388; 35 (iii) PMC6716529; 36 (iv) PMC8276422; 37 (v) PMC6309793. 38 Mental health research area. We realized 09 publications from the MURTI trainees in this area: (i) PMC6036650; 39 (ii) PMC5411062; 40 (iii) PMC6289958; 41 (iv) PMC6774805; 42 (v) PMC6613367; 43 (vi) PMC5423027; 44 (vii) PMC6614012; 20 (viii) PMC7750070; 45 (ix) 10.11604/pamj-oh.2020.3.9.25146.…”
Section: Resultsmentioning
confidence: 99%
“…We realized 05 publications from the MURTI trainees in this area: (i) PMC5659749; 34 (ii) PMC7341388; 35 (iii) PMC6716529; 36 (iv) PMC8276422; 37 (v) PMC6309793. 38 …”
Section: Resultsmentioning
confidence: 99%